Measuring Iran's success in achieving Millennium Development Goal 4: a systematic analysis of under-5 mortality at national and subnational levels from 1990 to 2015. Issue 5 (May 2017) - Mohammadi, Younes; Parsaeian, Mahboubeh; Mehdipour, Parinaz; Khosravi, Ardeshir; Larijani, Bagher; Sheidaei, Ali; Mansouri, Anita; Kasaeian, Amir; Yazdani, Kamran; Moradi-Lakeh, Maziar; Kazemi, Elaheh; Aghamohamadi, Saeide; et al.
Summary: Background: Child mortality as one of the key Millennium Development Goals (MDG 4—to reduce child mortality by two-thirds from 1990 to 2015), is included in the Sustainable Development Goals (SDG 3, target 2—to reduce child mortality to fewer than 25 deaths per 1000 livebirths for all countries by 2030), and is a key indicator of the health system in every country. In this study, we aimed to estimate the level and trend of child mortality from 1990 to 2015 in Iran, to assess the progress of the country and its provinces toward these goals. Methods: We used three different data sources: three censuses, a Demographic and Health Survey (DHS), and 5-year data from the death registration system. We used the summary birth history data from four data sources (the three censuses and DHS) and used maternal age cohort and maternal age period methods to estimate the trends in child mortality rates, combining the estimates of these two indirect methods using Loess regression. We also used the complete birth history method to estimate child mortality rate directly from DHS data. Finally, to synthesise different trends into a single trend and calculate uncertainty intervals (UI), we used Gaussian process regression. Findings: Under-5 mortality rates (deaths per 1000 livebirths) at the national level in Iran in 1990, 2000, 2010, and 2015 were 63·6 (95% UI 63·1–64·0), 38·8 (38·5–39·2), 24·9 (24·3–25·4), and 19·4 (18·6–20·2), respectively. Between 1990 and 2015, the median annual reduction and total overall reduction in these rates were 4·9% and 70%, respectively. At the provincial level, the difference between the highest and lowest child mortality rates in 1990, 2000, and 2015 were 65·6, 40·4, and 38·1 per 1000 livebirths, respectively. Based on the MDG 4 goal, five provinces had not decreased child mortality by two-thirds by 2015. Furthermore, six provinces had not reached SDG 3 (target 2). Interpretation: Iran and most of its provinces achieved MDG 4 and SDG 3 (target 2) goals by 2015. However, at the subnational level in some provinces, there is substantial inequity. Local policy makers should use effective strategies to accelerate the reduction of child mortality for these provinces by 2030. Possible recommendations for such strategies include enhancing the level of education and health literacy among women, tackling sex discrimination, and improving incomes for families. Funding: Iran Ministry of Health and Education.